PENERAPAN METODE PEMBIASAAN DALAM MENINGKATKAN NILAI SPRITUAL SISWA PADA PEMBELAJARAN PAI DI SDN 40 LEWIRATO - Salaini; Wahyuningsi; Nasaruddin (STKIP Subang, 2025)
This study aims to examine how the habituation method can enhance the spiritual values of students. Thus, it is expected that students will not only understand religious theories but also apply those values in their daily lives. The habituation method is expected to assist PAI (Islamic Religious Education) teachers at SDN 40 Lewirato in supporting the consistent development of students' spiritual character. In this study, a qualitative research method was used with techniques such as interviews, observations, and documentation for data collection. In the interview technique, several people were interviewed, including the PAI teacher and ten students. The research findings indicate that the habituation method can improve spiritual values, based on interview and observation results, through observations of how students are highly focused during the teaching and learning activities when the habituation method is applied. Furthermore, the interview results show that students become more respectful, honest, and accustomed to greeting others. However, the success of this method depends on supporting factors such as teaching media and the willingness of students.